Management of Isoniazid Monoresistant Tuberculosis - Yandhi, Rama; Zen Ahmad (HM Publisher, 2024)
lsoniazid (INH) is one of the main first-line drugs used for the treatment of active tuberculosis (TB) and latent TB infection because it has bactericidal capabilities and a good level of safety. The presence of TB germs that are resistant to INH will reduce the effectiveness of TB treatment. The treatment mix for INH monoresistant TB patients is a combination of rifampicin (R), isoniazid (H), pyrazinamide (Z), ethambutol (E), and levofloxacin (Lfx) or R-H-Z-E-Lfx given for 6 months. If a health facility provides loose TB medication, the patient can be given a combination of treatment without INH (R-Z-E-Lfx). In conditions where the Lfx drug cannot be used because there is severe intolerance (serious adverse events) or there are contra indications, the treatment given is the R-H-Z-E combination for 6 months. Clinical monitoring for patients with INH monoresistant TB follows the same principles as treatment of drug-sensitive TB. In conclusion, the treatment guide for INH monoresistant TB patients is a combination of rifampicin (R), isoniazid (H), pyrazinamide (Z), ethambutol (E), and levofloxacin (Lfx) or R-H-Z-E-Lfx for 6 months.